Establishing Relations : Odd Craft, Part 7. - Jacobs, W. W. (William Wymark), 1863-1943; Owen, Will, 1869-1957 (Salt Lake City, UT : Project Gutenberg, 2004)
"Establishing Relations" by W. W. Jacobs is a humorous short story that likely dates back to the early 20th century. This narrative, characteristic of Jacobs' style, explores themes of mistaken identity and romantic pursuits amidst quaint social settings. The story follows Mr. Richard Catesby, a second officer on a ship, as he awkwardly attempts to charm a young woman while inadvertently entangling himself in humorous misunderstandings. In the tale, Mr. Catesby is immediately struck by the beauty of Prudence Truefitt, the daughter of a widow living in Bashford's Lane. After his attempts at courting her lead to a mistaken identity crisis$1 (Bwhere he is misidentified as her long-lost brother Fred$1 (Bcomedic chaos ensues. Catesby's awkward yet earnest advances are met with confusion and playful confrontations, especially when Mrs. Porter, a woman claiming to be his wife, arrives on the scene. The story weaves through Catesby's misadventures as he navigates the convoluted situation, showcasing Jacobs$1 (Bsignature wit and social commentary on romance and relationships. (This is an automatically generated summary.)s
Release date is 2004-04-01
Produced by David Widger
Keywords: Humorous stories, English; England -- Social life and customs -- Fiction; Sailors -- Fiction